2021
DOI: 10.1002/jso.26366
|View full text |Cite
|
Sign up to set email alerts
|

Tumor characteristics and clinical outcome of peritoneal metastasis of gastric origin treated with a hyperthermic intraperitoneal chemotherapy procedure in the PERISCOPE I trial

Abstract: Introduction The PERISCOPE I (Treatment of PERItoneal dissemination in Stomach Cancer patients with cytOreductive surgery and hyPErthermic intraperitoneal chemotherapy) study was conducted to investigate the safety and feasibility of hyperthermic intraperitoneal chemotherapy (HIPEC) in gastric cancer patients with limited peritoneal dissemination. In this study, tumor characteristics and clinical outcome of the patients treated in the PERISCOPE I trial were investigated. Methods Patients who had undergone the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
1
1
Order By: Relevance
“…This review reports the effect of prophylactic HIPEC on the overall metastasis rate and peritoneal metastasis rate, con rming that prophylactic HIPEC reduces the occurrence of gastric cancer metastasis and reduces the risk of death due to peritoneal metastasis. Koemans and his colleagues pointed out in a PERISCOPE I trial that HIPEC can improve the survival rate of patients with gastric cancer, but the control of recurrence rate is not ideal [59]. This is different from our results, which may be due to different inclusion criteria and PERISCOPE I trial.…”
Section: Discussioncontrasting
confidence: 97%
“…This review reports the effect of prophylactic HIPEC on the overall metastasis rate and peritoneal metastasis rate, con rming that prophylactic HIPEC reduces the occurrence of gastric cancer metastasis and reduces the risk of death due to peritoneal metastasis. Koemans and his colleagues pointed out in a PERISCOPE I trial that HIPEC can improve the survival rate of patients with gastric cancer, but the control of recurrence rate is not ideal [59]. This is different from our results, which may be due to different inclusion criteria and PERISCOPE I trial.…”
Section: Discussioncontrasting
confidence: 97%
“…Likewise, the PERISCOPE-I trial showed promising survival results in neo-adjuvant treated patients with limited peritoneal disease. This is currently being further investigated by the PERISCOPE-II trial [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both normothermic and hyperthermic intraperitoneal chemotherapy (HIPEC) have been introduced in order to potentially prolong survival after PM diagnosis. Although initially promising results were reported, HIPEC treatment may only be meaningful in highly selected patients with, for example, very limited peritoneal disease [11][12][13][14]. The currently ongoing PERISCOPE-II trial investigates the effect of cytoreductive surgery (CRS) and HIPEC after preoperative chemotherapy compared to palliative chemotherapy in gastric cancer patients with tumor positive cytology and/or limited peritoneal metastasis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most common chemotherapeutic agents used were Mitomycin C and Cisplatin, which were applied in 31 and 32 regimens, respectively. The doses of the applied agents were reported either as the whole dose for the procedure in milligrams (mg) (19 papers) [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], or in milligrams for the body surface area (mg/m 2 ) (26 papers) [ 11 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. One of the latter units was additionally expressed in terms of the volume of solution (mg/m 2 /L) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…De Roover et al reported that, in half of their cases ( n = 8), there was a need to shorten the duration of HIPEC due to central hyperthermia [ 37 ]. Some researchers (mainly in newer reports) shortened the HIPEC duration to 30 or 45 min [ 11 , 45 , 53 , 54 , 55 , 56 , 67 ]. The others did not seem to value and stick to the time frames, and applied HIPEC for a time frame that was not directly specified; they preferred to choose a time range somewhere within the 30–120 min time frame [ 22 , 27 , 28 , 30 , 31 , 34 , 39 , 40 , 41 , 60 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%